Venous Thromboembolism and Estrogen-Containing Gender-Affirming Hormone Therapy - Dix, Caroline; Moloney, Mollie; Tran, Huyen A.; McFadyen, James D. (Thrombosis and Haemostasis, 2023)
Gender-affirming therapy involves the use of hormones to develop the physical characteristics of the identified gender and suppressing endogenous sex hormone production. Venous thromboembolism (VTE) is a known risk of exogenous estrogen therapy, and while evidence of VTE risk among transgender women using modern gender-affirming hormone therapy (GAHT) is still emerging, it is thought to affect up to 5% of transgender women. Historically, GAHT was associated with a high risk of VTE; however, modern preparations are less thrombogenic mainly due to significantly lower doses used as well as different preparations. This review presents the available literature regarding the following four topics: (1) risk of VTE among transgender women receiving estradiol GAHT, (2) how the route of administration of estradiol affects the VTE risk, (3) perioperative management of GAHT, (4) VTE risk among adolescents on GAHT. There is a need for large, longitudinal studies of transgender women using GAHT to further characterize VTE risk and how this is affected by factors such as patient age, duration of GAHT use, tobacco use, body mass index, and comorbidities. Future studies in these areas could inform the development of clinical guidelines to improve the care of transgender people.
Keywords: transgender; estrogen; venous thromboembolism; hormone therapy; gender